“Grace Under Pressure”: How CEOs Use Serious Leisure to Cope With the Demands of Their Job - Bunea, Emilia (Frontiers in Psychology, 2020)
How CEOs use their leisure to help respond to the demands of their job is important for themselves, their employees and their organizations. This study shines light on this hardly explored subject by focusing on CEOs of major US companies and their “serious leisure”, the goal-oriented pursuit of a nonwork passion. Serious leisure is increasingly practiced by the population at large as well as by top leaders. This study is based on 16 interviews with “serious leisurite” CEOs of Fortune 500, S&P 500 or comparable organizations. Novel insights are brought into the ways in which CEOs believe their passionate nonwork pursuit supports not only coping with the strain of the top job, but also optimal functioning in it, as well as into how they perceive the demands of the CEO role. This work contributes to research on leader personal resources and leader effectiveness, executive job demands, as well as to the leisure-based recovery literature.